Making Good Decisions: The Influence of Culture, Attachment Style, Religiosity, Patriotism and Nationalism (Global Journal of Human-Social Science, 2012)
This study explored the conflict model of decision making Janis Mann 1977 in relation to culture attachment style religiosity patriotism and nationalism Two groups of university students from Australia n 135 and Singapore n 159 were invited to participate through the use of a web survey Vigilant decision making was higher and hyper-vigilant decision making was lower for Australian than for Singaporean respondents Vigilant decision making was negatively related to avoidant attachment style and blind patriotism while positively associated with constructive patriotism and civic content nationalism Vigilant decision making was predicted by gender female low avoidant attachment style civic nationalism and constructive patriotism Hyper-vigilant decision making was positively related to anxious and avoidant attachment style external religiosity blind patriotism traditional and civic nationalism while negatively related to constructive patriotism Hyper-vigilance was predicted by gender female anxious and avoidant attachment style and extrinsic religiosity Buck-passing was positively associated with anxious and avoidant attachment style and civic nationalism Buck-passing was predicted by anxious and avoidant attachment style and by civic nationalism Procrastination was positively related to anxious and avoidant attachment style and was predicted by country Singapore and anxious and avoidant attachment style These results are explained in terms of decisions that are made around the world that may have broad ramifications including those relating to positions on refugees and terrorism
Keywords: Culture; attachment style; religiosity; patriotism; and nationalism